1993
DOI: 10.3146/i0095-3679-20-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 2,4-DB With Postemergence Graminicides

Abstract: Field experiments were conducted in North Carolina, Georgia, and Texas to determine if grass control is affected when postemergence-applied graminicides are mixed with 2,4-D B. Grass species evaluated included broadleaf signalgrass [Brachiaria platyphylla (Griseb.) Nash], goosegrass [Eleusine indica (L.) Gaertn.], johnsongrass [Sorghum halepense (L.) Pers.], large crabgrass [Digitaria sanguinalis (L.) Scop.], southern crabgrass [Digitaria ciliaris (Retz.) Koel.], and Texas panicum (Panicum texanum Bucld.). Mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Although pyrithiobac suppresses annual and perennial grasses, it can cause antagonism of graminicides (Ferreira and Coble 1994;Jordan et al 1993). In addition, the phenoxy herbicide 2,4-DB can reduce efficacy of clethodim (York et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Although pyrithiobac suppresses annual and perennial grasses, it can cause antagonism of graminicides (Ferreira and Coble 1994;Jordan et al 1993). In addition, the phenoxy herbicide 2,4-DB can reduce efficacy of clethodim (York et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The 2,4-DB molecule is not readily absorbed or phytotoxic, but the secondary metabolite (2,4-D) resulting from beta oxidation is both mobile and phytotoxic (Wathana et al, 1972;Wehtje et al, 1992) in many species. Much research can be found that documents peanut plant injury and/or yield response to 2,4-DB and imazapic (Brecke and Stephenson, 2006;Grey and Wehtje, 2005;Grichar, 2007;Hicks et al, 1998;Wehtje et al, 1993;York et al, 1993), however, little research has been reported on the effects that herbicides may have on seed quality. Lancaster et al (2005) reported that 2,4-DB reduced seed germination of sickelpod (Senna obtusifolia L. Irwin and Barneby) 30 to 40% when applied just prior to flowering or during peak flowering.…”
mentioning
confidence: 99%
“…Studies on the control of annual grasses in peanut generally focus on herbicide combinations and their interactions (Burke et al 2004;Grichar et al 2002;York et al 1993) or control with PRE herbicides (Brecke and Currey 1980;Grichar et al 1994;Johnson et al 2002;Prostko et al 2001). However, when POST applications of graminicides were delayed 2 wk, from 3 WAP to 5 WAP, peanut yields were reduced up to 1,800 kg/ha depending on rate and herbicide (Grichar and Boswell 1986).…”
Section: Resultsmentioning
confidence: 99%